Employee Competency in Improving Services in Ilangata Village, Anggrek District, North Gorontalo Regency - Sarwin Ishak; Lisda Van Gobel; Sofyan Alhadar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find out and obtain an objective picture about examining in more depth. This type of research is a descriptive research conducted using qualitative methods. Based on the results of the study it can be concluded that the discipline of the ilangata village officials in the hours of entering and leaving work has not run optimally and in accordance with the provisions of the applicable rules. several village officials arrived late and did not go home according to regulations, the education of village officials in ilangata on average had a high school education equivalent and one bachelor degree met the requirements. However, the problem is regarding skills, where some village officials in Ilangata are less skilled, as well as service support infrastructure in Langata Village, which is lacking and needs to be added. It is suggested that it is necessary to improve discipline and improve skills by participating in BIMTEK in order to provide optimal service to the community.